ESTIMATION OF GROUNDWATER RECHARGE IN BADRA-JASSAN BASIN USING ANNUAL WATER SURPLUS METHOD - Al-Shamaa, Issar; Ali, Batool (Iraqi Journal of Science, 2024)
Badra - Jassan basin is one of the Iraqi border basins which recently has beenreconstructed of its regions and expanded of its irrigated land to serve the Citizens ofthe area. In terms of hydrological condition, Galal Badra River Basin is divided intotwo parts where the first part located in Iran, and this part supports most of thedischarge of the river basin according to achieved runoff within the area. Secondpart of the river basin is located in Iraq covering area of (300 km2). Depending onclimate data measured in Badra meteorological station for the period (2001-1994),the climate was characterized to be continental semi-arid with annual total rainfallreached (221) mm and the evaporation from basin class A reached (3156) mm.Water balance were calculated in the basin using two methods, the first one dependson monthly averages for rainfall and actual evapotranspiration during the period(2001-1994). While in the second method, the water surplus was calculateddepending on calculation of each parameter in each year separately and usemathematical formula to calculate the runoff achieved in River basin of Badra. The